Autour du musée Albert-Kahn. Exposer à partir d’une collection de films. Un essai - Gilles Baud-Berthier (Conserveries Mémorielles)
The article deals with the difficult art of exhibiting films in museum exhibitions. First, the life of Albert Kahn (1860-1940), the man to which a museum is dedicated in France, is questionned, the focus in the biography of this self-made banker and pacifist being put on the intellectual influences that might have shaped his vision of the world and of his time. Then are examined several features of his work, especially the part played by the unique collection of pictures he called the Archives of the Planet, collected around the world between 1908 and 1931 by his staff of professional photographers and cameramen. Finally are examined the status of the films in the Archives of the Planet, the meaning Albert Kahn intended to give them and the links between these films, now protected inside a museum collection, and the way the museum satisfies the requirements of exhibitions for a large public.